Chapter 12 Bridging the Divide - Kind, Amy (Taylor & Francis, 2022)
Ch. 12 Can one have imaginative access to experiential perspectives vastly different from one s own? Can one successfully imagine what it s like to live a life very different from one s own? These questions are particularly pressing in contemporary society as we try to bridge racial, ethnic, and gender divides. Yet philosophers have often expressed considerable pessimism in this regard. It is often thought that the gulf between vastly different experiential perspectives cannot be bridged. This chapter explores the case for this pessimism. Though the case is often less implicit, the chapter identifies two different arguments that can be found in the literature: the Epistemic Arrogance argument and the Too Big a Gulf argument. Both arguments are found to be considerably weaker than is usually thought. But even if the case for pessimism is unsuccessful, discussion of that case suggests the importance of treading carefully in taking up imaginative explorations of different experiential perspectives. The chapter thus concludes with a cautionary note in this regard.